Trust Transfer and Swift Guanxi in Driving Customer Engagement on Live Streaming Commerce Platforms in Indonesia - Aflah Hanif Hariadi (MAN 4 Kota Pekanbaru, 2026)
This study examines the relationship between swift guanxi and customer engagement in live streaming commerce and customer trust. The focus of this study is the trust in broadcasters, community members, and products on Indonesian platforms such as Shopee Live, TikTok Live, Lazada Live, and Tokopedia Play. An online survey was used to gather quantitative data from 270 active users, and Partial Least Squares-Structural Equation Modeling (PLS-SEM) was used for analysis. This study offers a thorough model, indicating that trust in broadcasters and community members significantly enhances customer engagement, while trust in product does not directly influence engagement but positively impacts swift guanxi. Furthermore, the PLS-SEM results prove that trust in broadcasters as the central anchor in the live streaming ecosystem greatly transfers trust to both community members and products. Ultimately, swift guanxi plays a pivotal role in driving customer engagement.